Give My Poor Heart Ease : Voices of the Mississippi Blues - Ferris, William R. (Book collections on Project MUSE., 2009)
Throughout the 1960s and 1970s, folklorist William Ferris toured his home state of Mississippi, documenting the voices of African Americans as they spoke about and performed the diverse musical traditions that form the authentic roots of the blues. Illustrated with Ferris's photographs of the musicians and their communities and including a dual CD/DVD that presents his original field recordings and films, this book features more than 20 interviews relating frank, dramatic, and engaging narratives about black life and blues music in the heart of the American South. Oversize, with 45 halftones a.